Slovensko špranja in sorodno - Furlan, Metka (Slavia Centralis, 2020)
Slovenian špranja and relatedSlovenian špránja 'crack' and Croatian šprȁnja 'wood chip' derive from the PSl. nomen actionis *čь-pőrni (f.) 'splitting' from the prefixed verb *čь-pőr-ti, which was synonymous with PSl. *pőr-ti 'prick, separate, cleave, rip', cf. Rus. porótь, pórešь 'rip', Sln. práti, pọrjem/pórjem 'rip, tear'.
Keywords: etymology; word formation; semantics; expressive prefix